الاستخدامات الخاطئة للدلالة الإحصائية وحلول مقترحة = The misuses of the statistical significance and suggested solutions - Saied, Ebrahim; Al-Hidabi, Dawood Abdulmalek Yahya; Ali, Husin (الجمعية العراقية للدراسات التربوية و النفسية, 2020)
ىجفت الجراسة الحالية إلى تػضيح جػانب القرػر السختمفة التي تعاني مشيا الجاللة اإلحرائية في تفديخ نتائج الجراسات والبحػث، وتحجيج سػء استخجاـ الجاللة اإلحرائية في تفديخ الشتائج واقتخاح بعس الحمػؿ الشطخية لتصػيخ استخجاـ الجاللة اإلحرائية، أضيخت الشتائج أف أىع جػانب القرػر في الجاللة اإلحرائية ىػ تأثخ ىا بحجع العيشة والصبيعة الثشائية لشتائج الجاللة اإلحرائية، وكحلظ مشصكية الفخضية ًز الرفخية، ا وث االستخجامات الخاشئة لمجاللة اإلحرائية في الجراسات والبحػث والتي مغ ّقت الج ارسة أي أىسيا استخجاـ نتائج الجاللة اإلحرائية كأساس لذخح أىسية الشتائج، واإلشارة إلى األىسية العسمية لمشتائج، والتحقق مغ صحة الفخضية الرفخية، واقتخحت الجراسة مجسػعة مغ الحمػؿ لالستخجامات الرحيحة لمجاللة اإلحرائية مثل عجـ االعتساد عمى الشتائج في تقييع البحػث والجراسات، والرياغة السشاسبة ألسئمة البحث وفخضياتو، وذلظ باستخجاـ مؤشخات ذات أىسية عسمية وقجرة إحرائية باستخجاـ تحميل السشفعة العسمية أو الجاللة اإلكميشيكية. ***************************************************************************** This present study aimed at clarifying the various shortcomings of the statistical significance in interpreting the results of studies and research,identifying the misuses of the statistical significance in the interpretation of the results, and proposing some theoretical solutions to enhance the use of statistical significance. Results showed that the most important shortcoming in the statistical significance are related to the effect of the sample size on the statistical significance, the binary status of the results of the statistical significance, and the logic of the null hypothesis. The study has also documented some of the misuses of the statistical significance in research such as the use of statistically significant results as a basis to explain the importance of the results, indicate the practical significance of the results, and validate the null hypothesis. The study proposed a range of solutions for the correct uses of the statistical significance such as not to rely on the results in the evaluation of research and studies, appropriate phrasing of the research questions and hypotheses, using indicators of practical significance and statistical power, and using analysis of practical benefit or clinical significance.